The Implementation of Restorative Justice in the Resolution of Criminal Assault Cases: A Case Study at the Tanah Karo Police Department - Jimmy Primsa Sinuhaji; Maslon Hutabalian; Rayani Saragih (Indonesian Journal of Advanced Research, 2026)
The paradigm shift in criminal law from retributive justice focused on punishment towards restorative justice represents a progressive milestone in reinforcing social utility and public peace. This study aims to evaluate and analyze the structural implementation of restorative justice mechanisms in treating criminal assault cases within the Karo Regency Regional Police (Polres Tanah Karo), while specifying the empirical constraints encountered during enforcement. An empirical-juridical framework combined with a legal sociology approach was selected. Primary datasets were aggregated via exhaustive interviews with law enforcement investigators at the Satreskrim unit of Polres Tanah Karo, whereas secondary insights were derived from statutory laws and case records. The content analysis followed a qualitative methodology. The investigation concludes that Polres Tanah Karo successfully operationalized restorative justice for minor assault cases, complying with National Police Regulation No. 8 of 2021, interconnected with local Karo sociocultural customary norms. Settlements were finalized through penal mediation engaging victims, offenders, and community elders. Nonetheless, the full optimization of this non-litigious process remains hampered by internal psychological barriers, intense victim trauma, irrational financial compensations demanded, and insufficient awareness among rural communities concerning restorative principles.